Childhood Memory Reconstruction through a Surrealistic Approach as an Idea for Sculpture Creation - Mulyoho, Adi Sadewo; Warsono, Warsono; Rosidi, Muhammad Rain (Journal of Contemporary Indonesian Art, 2025)
Sculpture is a three-dimensional work that reflects the expression of its artist, involving feelings, imagination, and memories visualized in the work. This research explores the process of childhood memory reconstruction as a foundation for sculpture creation, and analyzes how personal experiences can be transformed into three-dimensional works with aesthetic value and visual narrative. The creation method uses a practice-based research approach with assemblage techniques that combine multiplex material and used drums, processed through stages of contemplation, idea emergence, to the embodiment of three-dimensional forms with a surrealistic style. The research results produced a series of sculptures representing various spectrums of childhood experiences, from happy moments to trauma, visualized through compositions of organic forms, layered textures, and the use of contrasting colors. Through the process of memory reconstruction, this research shows that personal experiences can be processed into creative energy and embodied in visual forms that have artistic value.